ANALISIS SIRKUMSTAN PADA BUKU CERITA ANAK THE 7 HABBITS OF HAPPY KIDS KARYA SEAN COVEY DAN TERJEMAHANNYA (Kajian Terjemahan dengan Pendekatan Systemic Functional Linguistics) - Sholihah, Husna Imro’athush; Santosa, Riyadi; Djatmika, Djatmika (Center of Language and Cultural Studies, 2018)
This research investigated the form and types of circumstances, translation techniques, translation quality of circumstances, and the impact of translation techniques towards the form, types and translation quality of circumstances in bilingual kids story book. This qualitative research used systemic functional linguistic approach. The data obtained was analyzed using analysis technique of Spradley. The results show that circumstances were expressed in the form of words, group of words, and prepositional phrases, having 7 types: circumstances of location, circumstances of manner, circumstances of extent, circumstances of causes, circumstances of accompaniment, circumstances of role, and circumstances of matter. The translation techniques include: single variant, couplet, triplet and quartet. Children stories vary in types and forms of circumstances, depending on the focus and plot of the stories. The translation techniques lead to either cause translation shift or translation qualities of the circumstances are of good quality in terms of accuracy, acceptability and high readability.